2008
DOI: 10.1097/smj.0b013e31817c74c3
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Prostatic Carcinoma Presenting as Fulminant Hepatic Failure

Abstract: A 68-year-old male presented with progressive abdominal pain, dyspnea, weight loss, and dysuria. Lab work revealed elevated creatine phosphokinase levels, prostate-specific antigen level (approximately 60 ng/mL), and elevated liver enzymes. He was admitted to the intensive care unit for worsening respiratory distress and confusion. He continued to deteriorate, and his bilirubin peaked at 8.5 mg/dL. The patient subsequently died, and an autopsy revealed extensive hepatic necrosis with diffuse intravascular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Radiologically occult liver metastasis usually occurs as diffuse malignant infiltration of the liver. This has been reported in the literature secondary to metastases from breast and lung carcinomas, prostate and urothelial carciomas, carcinomas of unknown primary origin and hematologic malignancies such as Hodgkin and Non-Hodgkin lymphomas [11][12][13][14][15][16]. USG and CT scans of the liver were reported as normal in almost all of these reported cases as it was in our case.…”
Section: Discussionsupporting
confidence: 75%
“…Radiologically occult liver metastasis usually occurs as diffuse malignant infiltration of the liver. This has been reported in the literature secondary to metastases from breast and lung carcinomas, prostate and urothelial carciomas, carcinomas of unknown primary origin and hematologic malignancies such as Hodgkin and Non-Hodgkin lymphomas [11][12][13][14][15][16]. USG and CT scans of the liver were reported as normal in almost all of these reported cases as it was in our case.…”
Section: Discussionsupporting
confidence: 75%
“…In severe cases with rapidly growing tumors, patients can present with FHF and subsequent multisystem organ failure as a result of homogenous infiltration of the liver by metastatic disease. Shakir [16] presented a case of metastatic prostate adenocarcinoma in which a 68-year-old man presented with FHF. An abdominal CT scan revealed hepatomegaly without focal lesions, and Doppler ultrasound showed hepatomegaly and hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case that they reported there was a good response to chemotherapy with improvement in the clinical status and liver function panel [4]. Shakir et al reported a case of fulminant hepatic failure in a patient with metastatic prostate cancer [5]. Depending on the severity of malignant infiltration obstructing the hepatic vasculature patient can present with features of hepatic ischemic injury, necrosis, and hepatic failure.…”
Section: Discussionmentioning
confidence: 99%